2019
DOI: 10.1021/acs.macromol.9b00495
|View full text |Cite
|
Sign up to set email alerts
|

Improving Electron Transport in a Double-Cable Conjugated Polymer via Parallel Perylenetriimide Design

Abstract: Double-cable conjugated polymer can be applied to single-component organic solar cells (SCOSCs), which have great potential to improve the stability and to simplify the fabrication procedure compared to two-component organic solar cells. However, SCOSCs always show low power-conversion efficiencies (PCEs), which is mainly due to the difficulty to tune the nanophase separation in double-cable polymers for charge transport. Herein, we are able to find a way to improve the electron transport in double-cable polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 59 publications
(86 reference statements)
0
24
0
Order By: Relevance
“…Over the past two decades, several research groups, including our own, have been studying new materials that covalently anchor the electron donor (D) and acceptor (A) moieties . PSCs bearing above‐mentioned materials have recently been studied in two main forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, several research groups, including our own, have been studying new materials that covalently anchor the electron donor (D) and acceptor (A) moieties . PSCs bearing above‐mentioned materials have recently been studied in two main forms.…”
Section: Introductionmentioning
confidence: 99%
“…PSCs bearing above‐mentioned materials have recently been studied in two main forms. One is a double‐cabled polymer composed mainly of a small conjugated molecular acceptor bound to the side chains of a main chain conjugated polymer donor . The other is a conjugated block copolymer (CBCP) combining the donor block (DB) and the acceptor block (AB) in a polymer chain .…”
Section: Introductionmentioning
confidence: 99%
“…BPTI unit as an π-extended PDI exhibits deep frontier energy levels and strong crystallinity, which can be potentially used as electron transporting material. [51] The targeted hybrid material CTOC-3-BPTI (Scheme 1) was simply synthesized via ligand exchange between BPTI-OH and ethylene glycolates in CTOC-3. CTOC-3-BPTI was then applied as interlayer into PSCs and OSCs, exhibiting enhanced PCEs over 20% and 16%.…”
Section: Introductionmentioning
confidence: 99%
“…We have been particularly interested in double‐cable conjugated polymers for application in SCOSCs since they could be synthesized via a controllable manner, in which a series of functionalized monomers with pendent electron acceptors were prepared for palladium‐catalyzed polymerization [11] . This enabled us to incorporate the widely reported conjugated polymers and electron acceptors into double‐cable polymers, providing tunable optical and electrical properties [7h–m, 12] . Among them, we found that the linear conjugated backbones [7h] and post‐thermal treatment [7i] could facilitate the simultaneous self‐assembly of conjugated backbones and aromatic side units, generated well‐ordered nanophase separation, and hence provided external quantum efficiencies (EQEs) above 0.65 and PCEs over 6 %.…”
Section: Introductionmentioning
confidence: 99%